General equilibrium theory : an introduction - Starr, Ross M. (Cambridge : Cambridge University Press, 2011)
General Equilibrium Theory: An Introduction presents the mathematical economic theory of price determination and resource allocation from elementary to advanced levels, suitable for advanced undergraduates and graduate students of economics. This Arrow-Debreu model (known for two of its most prominent founders, both Nobel Laureates) is the basis of modern price theory and of a wide range of applications. The new edition updates discussion throughout and expands the number and variety of exercises. It offers a revised and extended treatment of core convergence, including the case of non-convex preferences, and introduces the investigation of approximate equilibrium with U-shaped curves and non-convex preferences.
Machine generated contents note: Part I. General Equilibrium Theory: Getting Acquainted: 1. Concept and history of general equilibrium theory; 2. An elementary general equilibrium model -- the Robinson Crusoe economy; 3. The Edgeworth box; 4. Integrating production and multiple consumption decisions: a 2 x 2 x 2 model; 5. Existence of general equilibrium in an economy with an excess demand function; Part II. Mathematics: 6. Logic and set theory; 7. RN: real N-dimensional Euclidean space; 8. Convex sets, separation theorems, and non-convex sets in RN; 9. The Brouwer fixed point theorem; Part III. An Economy with Bounded Production Technology, Supply and Demand Functions: 10. Markets, prices, commodities, and mathematical economic theory; 11. Production with bounded firm technology; 12. Households; 13. A market economy; 14. General equilibrium of the market economy with an excess demand function; Part IV. An Economy with Unbounded Production Technology, Supply and Demand Functions: 15. Theory of production: the unbounded technology case; 16. Households: the unbounded technology case; 17. A market economy: the unbounded technology case; 18. General equilibrium of the market economy: the unbounded technology case; Part V. Welfare Economics and the Scope of Markets: 19. Pareto efficiency and competitive equilibrium; 20. Time and uncertainty: futures markets; Part VI. Bargaining and Equilibrium: The Core: 21. The core of a market economy; 22. Convergence of the core of a large economy; Part VII. An Economy with Supply and Demand Correspondences: 23. Mathematics: analysis of point to set mappings; 24. General equilibrium of the market economy with an excess demand correspondence; 25. U-shaped cost curves and concentrated preferences; Part VIII. Standing on the Shoulders of Giants: 26. Next steps; 27. Summary and conclusion.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Equilibrium (Economics); Economics, Mathematical